Urgensi Perbaikan Generasi melalui Pendidikan Pranikah - Ishaq Syahid (Departement of Mathematics Education, 2023)
Today's life is so influenced by the hydonist lifestyle that we forget to prepare a superior generation. Therefore, for those who already have a family plus descendants, they should always look after and guide their family members so that later they can be held accountable when facing the Divine. There are many problems in starting a family that become obstacles to preparing a golden generation, namely due to early marriage and divorce. It is through education that children can be led to a better life, whether biologically, psychologically or religiously. And the most important education that needs to be strongly strengthened is family education because it will be the foundation for later life. To grow a superior generation starting from superior seeds, starting from choosing a partner according to the criteria recommended by religion, so the implementation of the stages of marriage must not be separated from the norms that already exist in the religion. the rest of this is that after a valid marriage contract has been entered into, the head of the family has an obligation towards himself and his family. This obligation is viewed from several angles: normative, juridical, psychological and sociological.